Analysis of Energy Consumption for a Distributed Database System Using Smartphone in Cellular Network - Wankhade, Nitin V; Deshpande, S.P (International Journal of Computer Sciences and Engineering, 2025)
Fast advancement in the technology offering much smarter functionalities giving tremendous increase in Smartphone users. The battery powered Smartphone is being used to keep people engaged, communicate and remain online throughout the day, no matter where they are located so the scarcity of power is also increased. The technology advancement speed of offering functionalities in the Smartphone is much faster than that of the technology for development in batteries. Most of the applications waste energy in rest condition. The power consumption for a Distributed database system “SmartSource” using Smartphone in cellular network has been analyzed in this paper. The performance evaluation of the consumption of energy for the system is tested and presented